Epistemologi Dalam Filsafat Barat - sari, diana ana (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2020)
Abstract: The presence of epistemology in western philosophy is very influential in life, especially in regulating the strategy of power or power to achieve goals. The style of western thought brought a big change in the knowledge of thinking, perspectives, and behavior that became the motors of civilization. Two main influential schools in the study of western philosophy such as rationalism and empiricism are conflicting. Both favor reason and five senses, but also inseparable from the weaknesses of each that will be revealed by researchers. Likewise the negative impact behind the superiority of western epistemology on the nature and development and existence of humans.